2015
DOI: 10.1117/1.jbo.20.11.111208
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional refractive index tomograms and deformability of individual human red blood cells from cord blood of newborn infants and maternal blood

Abstract: Red blood cells (RBCs) from the cord blood of newborn infants have distinctive functions in fetal and infant development. To systematically investigate the biophysical characteristics of individual cord RBCs in newborn infants, a comparative study was performed on RBCs from the cord blood of newborn infants and from adult mothers or nonpregnant women using optical holographic microtomography. Optical measurements of the distributions of the three-dimensional refractive indices and the dynamic membrane fluctuat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…Recently, it has been shown that QPI techniques can be used to precisely probe dynamic fluctuations in cell membranes 46 , and these have been utilised in diverse applications in infectious disease 17, 42 , sickle cell disease 47 , and haematology 19, 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that QPI techniques can be used to precisely probe dynamic fluctuations in cell membranes 46 , and these have been utilised in diverse applications in infectious disease 17, 42 , sickle cell disease 47 , and haematology 19, 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Measured 2-D optical phase delay of individual cells corresponds to the dry mass of each cell202122, which is the mass of the aqueous components inside the cell including proteins and subcellular organelles, and the temporal fluctuation of the optical phase delay is implemented to study the membrane fluctuation of biological cells on a nanometre level232425. Moreover, the measurements of multiple complex optical fields with various incident angles reconstruct the 3-D refractive index (RI) distribution of biological samples, which corresponds to the intracellular protein concentration of individual cell262728293031323334353637. The 3-D RI distribution of biological samples can serve as an alternate solution for 3-D label-free imaging and quantification of LDs in live cells.…”
mentioning
confidence: 99%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] however, we were unable to identify lymphocyte cell types due to their indistinguishable cellular morphology and biochemical characteristics.…”
Section: Identification Of Lymphocyte Cell Types Is Crucial For Undermentioning
confidence: 95%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%